The Influence of Recruitment and Training on Employee Performance through Job Satisfaction as an Intervening Variable at PT. XYZ in Riau - Cahyani, Fabelia Regina; Setiawati, Trias; Suratman, Andriyastuti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research is entitled "The Influence of Recruitment and Training on Employee Performance Through Job Satisfaction as an Intervening Variable at PT. The purpose of this research is to determine the mediating effect of job satisfaction in the relationship between recruitment and training on employee performance. This research uses a quantitative method and employs a questionnaire for data collection. This research uses a population of 200 employees. The sampling technique in this study employs a census method which is the sample collected on operational, funding, marketing and landing departments, with a sample size of 196 employees. This research uses path analysis, multiple linear regression analysis methods, t-tests. The research results show that recruitment has a positive and significant effect on employee performance, training has a positive and significant effect on employee performance, recruitment has a positive and significant effect on job satisfaction, training has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, job satisfaction can mediate the relationship between recruitment and employee performance, and job satisfaction can mediate the relationship between training and employee performance.